Retropupillary Iris-Claw Intraocular Lens Implantation in Aphakia Post-Endophthalmitis - Zahra, Alvi Laili; Audina, Rizna; Dharmawidiarini, Dini; Napitupulu, Sahata P. H. (Vision Science and Eye Health Journal, 2025)
Introduction: Endophthalmitis is a severe eye disease. Due to the previous condition, selecting the appropriate type of secondary intraocular lens (IOL) is challenging. The Objective of this report is to describe the outcome of retropupillary iris-claw intraocular lens (RP- ICIOL) implantation to treat aphakia in patients with low corneal endothelial cell count, lack of capsular support, and a history of endophthalmitis. Case Presentation: A 73-year-old female patient reported experiencing hazy vision in her right eye (RE) for four months following cataract surgery. The patient had previously been diagnosed with aphakia and endophthalmitis RE and was admitted for three days. The visual acuity of the RE was 1/60. On anterior segment examination, the cornea was clear, the anterior chamber was deep, there was no flare or cell, vitreous strands were present in the anterior chamber, and the pupil was irregular with an aphakic lens. Examination of the posterior segment was within normal limits. Specular microscopy showing corneal endothelial cell density (CECD) of RE was 1086 cells/mm2. The patient then underwent RP-ICIOL implantation. Post-operatively, the visual acuity of the RE improved to 6/25, and the intraocular pressure (IOP) was 11 mmHg, as measured using non-contact tonometry. Three months post-op, the visual acuity was 6/30, the IOP was 17 mmHg in the RE and the CECD was 1108 cells/mm2. Conclusions: Good and appropriate management of endophthalmitis can save a patient's vision. Secondary iris-claw IOL implantation is a viable treatment option for aphakia following endophthalmitis, offering the advantage of maintaining the physiologic posterior position and being minimally invasive.